SOSIALISASI APLIKASI KEUANGAN UNTUK MENINGKATKAN KINERJA UMKM WARUNG AYAM PENYET BERKAH - Rahmawaty Hasibuan; Martalina Situmorang; Chris Dayanti Br. Ginting (Universitas Pahlawan Tuanku Tambusai, 2022)
Against the background of the awareness that financial records really need to be done to advance business, we are conducting socialization activities for one of the accounting recording applications, namely the